Not all stars form in clusters -: Gaia-DR2 uncovers the origin of OB associations - Ward, Jacob L.; Kruijssen, Diederik; Rix, Hans-Walter (Monthly notices of the Royal Astronomical Society, 2020)
Historically, it has often been asserted that most stars form in compact clusters. In this scenario, present-day gravitationally unbound OB associations are the result of the expansion of initially gravitationally bound star clusters. However, this paradigm is inconsistent with recent results, both theoretical and observational, that instead favour a hierarchical picture of star formation in which stars are formed across a continuous distribution of gas densities and most OB associations never were bound clusters. Instead they are formed in situ as the low-density side of this distribution, rather than as the remnants of expanding clusters. We utilize the second Gaia data release to quantify the degree to which OB associations are undergoing expansion and, therefore, whether OB associations are the product of expanding clusters, or whether they were born in situ, as the large-scale globally unbound associations that we see today. We ﬁnd that the observed kinematic properties of associations are consistent with highly substructured velocity ﬁelds and additionally require some degree of localized expansion from subclusters within the association. While most present-day OB associations do exhibit low levels of expansion, there is no signiﬁcant correlation between radial velocity and radius. Therefore, the large-scale structure of associations is not set by the expansion of clusters, rather it is a relic of the molecular gas cloud from which the association was formed. This ﬁnding is inconsistent with a monolithic model of association formation and instead favours a hierarchical model, in which OB associations form in situ, following the fractal structure of the gas from which they form.